Immunogenicity Parameters of Cancer Patients Receiving the mRNA Vaccine BNT162b2 While Obtaining Radiotherapy: A Longitudinal Cohort Evaluation - Paul Thöne; Margot Egger; Marija Geroldinger-Simic; Harald Kindermann; Lukas Kocik; Nicola Karasek; Barbara Fischerlehner; Kurt Spiegl; Georg Gruber; Bernhard Aschacher; Benjamin Dieplinger; Martin Clodi; et al. (Vaccines, 2024)
Background: Cancer patients are highly prone to infectious diseases. While undergoing antineoplastic treatment, the risk of severe symptoms upon infection increases, necessitating efficient protective measures, such as vaccination. For patients receiving radiotherapy, there is no specific information about humoral immunity. During the COVID-19 pandemic, serial antibody measurements were therefore offered to cancer patients, following SARS-CoV-2 vaccination while obtaining radiotherapy. Methods: Out of 74 enrolled patients, 46 met the inclusion criteria. Two cohorts were allocated, depending on an association with chemotherapy or pure radiotherapy. An additional healthy control cohort of 16 healthcare workers was enrolled. All participants followed a two-fold BNT162b2 vaccine schedule. SARS-CoV-2 binding antibodies were measured serially in a 7-day cycle for 35 days and over the long-term, using the Elecsys® Anti-SARS-CoV-2 immunoassay. Results: Cancer patients under pure radiotherapy have a comparable humoral vaccination response and long-term persistency of antibodies to healthy controls. Patients receiving additional chemotherapy show a significantly delayed immune response and decreased antibody titers. The vaccine was well tolerated in all cohorts. Conclusions: Pure radiotherapy in cancer patients does not interfere with the vaccine-induced humoral immune response or other immunogenetic aspects, whereas previous or simultaneous chemotherapy does. Findings are of particular relevance for future epidemic or pandemic scenarios.